2021
DOI: 10.1021/acsabm.0c01597
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Doped Carbon Dots with Redshifted Orange Emission for Enhanced Fluorescence and Magnetic Resonance Imaging

Abstract: Metal-doped carbon dots (CDs) exhibited promising application in fluorescence and magnetic resonance (MR) imaging, but developing manganese-doped CDs (Mn-CDs) with long wavelength emission and enhanced MR performance is a challenge. Herein, using a one-step solvothermal method, Mn-CDs with redshifted orange emission and enhanced longitudinal relaxation were synthesized for fluorescence and MR imaging. The results indicated that the prepared Mn-CDs had a uniform size distribution, and the average size was 5 nm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Doping with metal atoms, such as Zn, Mg, Ag, Au, Cu, Ga, and Gd, in the carbon network may result in the perturbation of the crystal lattice of CDs alongside with appearance of additional energy levels (Figure 3a), which would alter both steady-state and time-resolved optical properties. [54] As an example, doping with Mn shifted the PL band of CDs to green, [92] orange, [93] red, [94] and even NIR [59] spectral region. Doping with lanthanides on the other hand may result in the appearance of their characteristic narrow PL lines, such as PL [38] Copyright 2017, Wiley-VCH.…”
Section: Steady-state Photoluminescencementioning
confidence: 99%
“…Doping with metal atoms, such as Zn, Mg, Ag, Au, Cu, Ga, and Gd, in the carbon network may result in the perturbation of the crystal lattice of CDs alongside with appearance of additional energy levels (Figure 3a), which would alter both steady-state and time-resolved optical properties. [54] As an example, doping with Mn shifted the PL band of CDs to green, [92] orange, [93] red, [94] and even NIR [59] spectral region. Doping with lanthanides on the other hand may result in the appearance of their characteristic narrow PL lines, such as PL [38] Copyright 2017, Wiley-VCH.…”
Section: Steady-state Photoluminescencementioning
confidence: 99%
“…Several bottom-up approaches have been extensively adopted for the creation of metal-doped CDs because of their low cost and better efficiency. CDs have been synthesized by solvothermal reactions of carbon-based materials and metallic salts to contain ions of silver [ 64 ], manganese [ 65 ], copper [ 49 ], magnesium [ 66 , 67 ], cobalt [ 68 ], zinc [ 69 ], gadolinium [ 28 , 70 ] and chromium [ 71 ]. As an example, aqueous GQDs (graphene quantum dots, which is the same as CDs) (0.1 mg/mL) were prepared by using an electrochemical cyclic voltammetry instrument [ 66 ].…”
Section: Synthesis Of Hybrid and Doped Cdsmentioning
confidence: 99%
“…266,267 Excitingly, studies showed that doping these ions on CDs could effectively reduce their leakage to a great extent, increase their longitudinal relaxation rate, and show a better magnetic resonance effect. 268–270 For instance, systems based on Gd–CD and Mn–CD composites have been developed and applied as MRI probes, respectively. 271,272 For the Gd–CDs as the MRI probe, it was observed that Gd–CDs were quickly excreted by the kidneys and accumulated in the bladder after 30 minutes of intravenous injection into the mice (Fig.…”
Section: Composites For Biomedical Applicationsmentioning
confidence: 99%
“…For instance, in Yan and co-workers’ study, glyoxylic acid-modified CDs (GA-CDs) were used as a FRET ratiometric fluorescent probe for the detection of Cu 2+ in aqueous solution. 388 Similarly, Chen et al also applied cyclam-functionalized CDs as a FRET nanoprobe for the detection of Cu 2+ and S. 2–389 In addition to the above examples, the detection of other important metal ions such as Ag + , Cu 2+ , Cr 6+ , and Pb 2+ has also been successfully realized with CD composite-based sensing platforms. 390–401…”
Section: Composites For Biomedical Applicationsmentioning
confidence: 99%